Direct and indirect estimation of adolescent sexual intercourse and contraceptive use in Rajasthan India: an application of the best friend methodology - Suzanne O. Bell; Danish Ahmad; Anoop Khanna; Haley L. Thomas; Caroline Moreau (BMC, 2024)
Abstract Background Existing estimates of adolescent sexual and reproductive health (ASRH) behaviors may be a gross undercount given the sensitivity of this behavior in Indian culture. The objective of this study was to estimate ASRH behaviors in Rajasthan, India using direct questions and the best friend approach that seeks to reduce social desirability bias. Methods We used population-based data of adolescents aged 15-19 in Rajasthan collected between September and December 2022. Data include whether the respondent and her closest female friend ever had a partner, ever had sex, ever used contraception, and were currently using contraception. We estimated respondent and best friend ASRH outcomes separately, overall and among unmarried adolescents for whom we anticipate social desirability bias is greatest. Results The best friend approach performed well, with method assumptions largely met even before adjustments. Respondent and best friend estimates were similar among all adolescents except for current contraceptive use, which was higher for friends (though not significantly so). However, we observed large differences in ASRH behaviors between unmarried respondents and friends, with a significantly higher percentage of friends who ever had a partner (4.3% respondents, 11.6% friends), and a slightly higher percentage who ever had sex (2.4%, 3.8%) and who were currently using contraception (17.0%, 19.7% among those in need of contraception). Conclusions We observed potential benefits of using the best friend methodology in estimating premarital sexual activity, but further work is needed to refine social network-based measures of sensitive adolescent behaviors in larger study samples to better understand ASRH needs.